Financing for Low-carbon Energy Transition Unlocking the Potential of Private Capital (Springer Singapore, 2018)
This book is the first comprehensive assessment of the state of low-carbon investments in Asia, analyzing the rationales, mandates and public-private financing activities. Based on the experiences of several regional initiatives wherein public financing is catalyzing private investments in low-carbon infrastructure, this book proposes a framework that can be used as a tool to identify factors that influence private investment decisions and policy instruments that can scale up the private capital. Placing the Asian economies onto a low-carbon development pathway requires an unprecedented shift in investments. This book addresses this situation by asking questions such as • What is the central role of private finance in achieving the Paris Agreement targets? • What key policy levers and risk mitigation can governments use in an effort to unlock the potentials of private capital? • How can regionally coordinated actions hold significant promise for scaling up private investments?